Sense Your Power : The ECO Approach to Energy Awareness for IoT Devices - Michel Rottleuthner and Thomas C. Schmidt and Matthias Wählisch (ACM transactions on embedded computing systems, 2021)
Energy-constrained sensor nodes can adaptively optimize their energy consumption if a continuous measurement is provided. This is of particular importance in scenarios of high dynamics such as with energy harvesting. Still, self-measuring of power consumption at reasonable cost and complexity is unavailable as a generic system service. In this article, we present ECO, a hardware-software co-design that adds autonomous energy management capabilities to a large class of low-end IoT devices. ECO consists of a highly portable hardware shield built from inexpensive commodity components and software integrated into the RIOT operating system. RIOT supports more than 200 popular microcontrollers. Leveraging this flexibility, we assembled a variety of sensor nodes to evaluate key performance properties for different device classes. An overview and comparison with related work shows how ECO fills the gap of in situ power attribution transparently for consumers and how it improves over existing solutions. We also report about two different real-world field trials, which validate our solution for long-term production use.
Keywords: Energy harvesting; energy management; IoT operating system; power measurement